The Securitization Of Human Trafficking In Indonesia - Rizal, Sukma (2016)
This paper looks at the problem of human trafficking in Indonesia and the response by state and non-state actors to the problem. It specifically analyses the nature of securitizing the problem in Indonesia by looking at the extent to which the problem has or has not been securitized by international, regional and national actors. The discussion is divided into four sections. The first section looks at the situation of human trafficking in Indonesia. The second section seeks to delineate specific strategies—either through speech acts or any other strategies—employed by international and national actors. The third section examines the Indonesian government’s response to the process of securitization by both international and national actors and assesses the adequacy of policy outcomes in Indonesia by looking at measures that have been carried out by the government in combating the problem of human trafficking. This section also looks at the domestic political context within which the securitization process has taken place, and explains the “securitization gap”, namely the disparity between the process of international and domestic securitization on the one hand and the gap between rhetoric and action on the other. In doing so, the paper seeks to explain why policy outcomes in Indonesia have not been adequate in combating the problem. The fourth section proceeds to provide an alternative path to securitization that can be taken up by securitizing actors in Indonesia in order to move the issue of combating human trafficking “beyond normal politics”.